Twisted Metal. - Shaw, Patrick
Sony's homicidal ice cream man and his band of degenerates return to recalm their crown as the kings of car combat.
Keywords: Twisted Metal 2 (Game); Sony video games; PlayStation; Vehicular combats; Da Vinci's war machines